2014
DOI: 10.3147/jsfp.49.53
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Viral Nervous Necrosis in Endangered Fish species Epinephelus costae and E. marginatus in Northern Tunisian Coasts

Abstract: 魚病研究 F i s h P a t h o l o g y , 4 9 ( 2 ) , 5 3 -5 6 , 2 0 1 4 . 6 © 2 0 1 4 T h e J a p a n e s e S o c i e t y o f F i s h P a t h o l o g y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
7
0
4
Order By: Relevance
“…In recent The RGNNV genotype, which affects tropical and temperate fish species, is the most widely distributed ( Figure 2) and has the highest number of susceptible species (Tables 1, 2 and 4). In recent years, surveys conducted in different geographical areas have shown that RGNNV is widely distributed Pathogens 2020, 9, 106 6 of 46 not only in farmed but also among wild fish in the Mediterranean basin and along the coasts of Asia and Australia [46,[62][63][64][65][66][67][68][69][70][71][72]. It has also been isolated from farmed white seabass (Atractoscion nobilis) in California [73].…”
Section: Geographical Distribution and Host Rangementioning
confidence: 99%
See 3 more Smart Citations
“…In recent The RGNNV genotype, which affects tropical and temperate fish species, is the most widely distributed ( Figure 2) and has the highest number of susceptible species (Tables 1, 2 and 4). In recent years, surveys conducted in different geographical areas have shown that RGNNV is widely distributed Pathogens 2020, 9, 106 6 of 46 not only in farmed but also among wild fish in the Mediterranean basin and along the coasts of Asia and Australia [46,[62][63][64][65][66][67][68][69][70][71][72]. It has also been isolated from farmed white seabass (Atractoscion nobilis) in California [73].…”
Section: Geographical Distribution and Host Rangementioning
confidence: 99%
“…It is well documented that changes experienced by ecosystems will affect the epidemiology of infectious diseases in animals, in the wild and under intensive farming conditions, including aquaculture [152][153][154][155][156]. The high number of wild asymptomatic species infected with NNV, mainly in Asian and Mediterranean countries [62,64,[66][67][68]71,80,82] and the quick rise in the viral load and subsequent outbreak of mortalities observed in experimentally infected sole when water temperature increased from 16 to 22 • C [148], suggest that VER outbreaks could have dramatic effects on natural populations, as has already been reported for some endangered fish species in the Mediterranean [72,96,109]. On the other hand, it could be argued that ocean warming could decrease the pathologies associated with the BFNNV genotype.…”
Section: Viral Thermotolerancementioning
confidence: 99%
See 2 more Smart Citations
“…Wild dusky grouper have been previously observed to suffer naturally occurring disease outbreaks (Vendramin et al 2013), with moribund and dead fish often observed to carry skin lesions, principally on the head. These are frequently associated with physical damage occurring as a consequence of loss of equilibrium brought about by nodaviral encephalitis (Marino & Azzuro 2001;Vendramin et al 2013;Haddad-Boubaker et al 2014;Kara et al 2014). In Libya, mass mortalities of a range of wild grouper species have been frequently reported (Southgate 1985).…”
Section: Introductionmentioning
confidence: 99%